Needs analysis in English specific purposes context: Non-English students as a case study - Dzul Rachman; Khusnul Khatimah; Syarief Fajaruddin; Godlove Elioth Kiswaga (Psychology, Evaluation, and Technology in Educational Research, 2022)
Globalization, on the other hand, necessitates the use of English scholarly for a multitude of objectives. With the exception of the oral presentation course, which was designed without undertaking needs analysis, English has been taught in traditional ways at universities. As a result, completing a systematic requirements analysis and identifying the challenges faced by Non-English major students necessitates investigation. The qualitative case study approach was used in this study, and the questionnaires were designed to extract information regarding the students' oral presentation demands. The questionnaire was filled out online by 164 people. According to the findings of the investigation, students in the ESP class regard oral presenting as a crucial component of their formal education. Furthermore, oral presentations have proven to be a good means of improving students' communication skills. As a result, student presentations have evolved into key components in providing positive learning experiences. This finding and conclusion, however, are limited to a specific department in a specific location and circumstance. The analysis results may differ depending on the field and circumstances. It is recommended that additional needs analysis research for other disciplines be conducted in greater depth.